Analisis Volume Lalu Lintas pada Jalan Raya Semolowaru Surabaya - Ardiansyah, Surya lham; Hartatik, Nurani; Rizkiardi, Aditya (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Semolowaru Highway is not free from challenges, such as traffic congestion during rush hour and the need for routine maintenance to maintain the safety and comfort of road users. Semolowaru Highway is included in the category of 4/2 TT type roads with a road width of 4 meters per lane limited by a median road width of 80 cm so that each direction of the lane is close to each other with a Road Length of 750 m. It is necessary to analyze the performance of road sections and traffic using manual counts on this road section. The method used in this study is quantitative with the approach of the Indonesian Road Capacity Guidelines (PKJI) 2023. Data acquisition comes from primary data and secondary data. The purpose of this study was to determine the traffic volume, the data used in this study is primary data. The results of the analysis show that the peak hour of traffic volume in direction A occurred on Friday, September 6, 2024 at 16.00-17.00 was 2360.95 skr / hour. Meanwhile, the peak traffic volume in direction B on Friday, September 6, 2024 at 16.00-17.00 was 2022.35 sec/hour.